Formative evaluation of a National Institutes of Health-funded translational research program for Doctor of Nursing Practice students. - Souffront, Kimberly; Cohen, Bevin (Nursing Outlook, 2026)
Cardiovascular disease (CVD) remains the leading cause of mortality in the United States, with hypertension disproportionately affecting historically disadvantaged groups. Doctor of Nursing Practice (DNP)-prepared nurses can bridge the gap between research and practice, yet structured translational research training remains scarce. The Translational Research and Implementation Science for Nurses (TRAIN) program was developed to equip underrepresented minority DNP students with research skills, mentorship, and hands-on experience to advance CVD health equity. TRAIN is a 12-week National Institutes of Health-funded fellowship combining hands-on research (70%) and classroom instruction (30%) under interdisciplinary faculty mentorship. The curriculum includes translational research methods, responsible conduct of research, and CVD health equity science. One-year evaluation showed improved research literacy, confidence, and professional networking. Challenges included recruitment, program buy-in, and short duration. TRAIN is a scalable model for DNP training in cardiovascular translational science, with future expansion planned for other chronic illnesses and mentorship. • First National Institutes of Health-funded training program for Doctor of Nursing Practice students. • Develops underrepresented nurse leaders to bridge the gap between evidence generation and clinical implementation. • Integrates classroom education and hands-on clinical research guided by expert mentors. • Provides a scalable framework for preparing Doctor of Nursing Practice nurses for research translation.